POSS Compounds as Modifiers for Rigid Polyurethane Foams (Composites) - Strąkowska, Anna (Polymers (Basel), 2019)
Three types of polyhedral oligomeric silsesquioxanes (POSSs) with different functional active groups were used to modify rigid polyurethane foams (RPUFs). Aminopropylisobutyl-POSS (AP-POSS), trisilanoisobutyl-POSS (TS-POSS) and octa(3-hydroxy-3-methylbutyldimethylsiloxy-POSS (OH-POSS) were added in an amount of 0.5 wt.% of the polyol weight. The characteristics of fillers including the size of particles, evaluation of the dispersion of particles and their effect on the viscosity of the polyol premixes were performed. Next, the obtained foams were evaluated by their processing parameters, morphology (Scanning Electron Microscopy analysis, SEM), mechanical properties (compressive test, three-point bending test, impact strength), viscoelastic behavior (Dynamic Mechanical Analysis, DMA), thermal properties (Thermogravimetric Analysis, TGA, thermal conductivity) and application properties (contact angle, water absorption). The results showed that the morphology of modified foams is significantly affected by the fillers typology, which resulted in inhomogeneous, irregular, large cell shapes and further affected the physical and mechanical properties of the resulting materials. RPUFs modified with AP-POSS represent better mechanical properties compared to the RPUFs modified with other POSS.